An approach to addressing rural depopulation in the black soil region: insights from the county urban–rural settlement system - Ma, Zuopeng; Tong, Yao; Liu, Jibin; Zhou, Guolei; Liu, Yanjun; Wen, Xin; Zhang, Pingyu (Frontiers in Sustainable Food Systems, 2025)
In the context of rural depopulation, spatial reorganization of settlements is widely recognized as a critical strategy to alleviate the human-land contradiction and enhance land use efficiency in the black-soil region. Using Yushu County as a case study, this paper explores an approach to the spatial optimization of urban–rural settlements in the black soil region. Currently, the urban–rural settlement system exhibits a distorted structure characterized by an excess of small settlements and a scarcity of large and medium-sized settlements, while the rank-size curve illustrates the phenomenon of “raising head, craning neck and drooping tail.” Rural development potential displays a pronounced high-high and low-low aggregation pattern. In light of this, the consolidation of settlements should be implemented at two scales: administrative villages and towns. In areas with high potential for rural development, merging natural settlements into the central settlement within an administrative village is recommended. In areas with low potential for rural development, the relocation and consolidation of natural settlements should be guided by the ideal service radius of central settlements within a town. This approach could preserve the original social relations to the greatest extent, thus facilitating the effective implementation of rural restructuring strategies.